Inequalities in healthcare access: how a man with exstrophy in rural India coped. (31st October 2018) - Pandey, Siddharth; Sharma, Deepanshu; Singh, Bhupender Pal; Goel, Apul
Abstract : We report a case of a 22-year-old man with adult exstrophy. The patient made a self-made urine collection device, which helped him to lead a normal life, carrying out his routine as well as occupational activities smoothly. This patient is a prime example of inequalities in healthcare distribution in low-income and middle-income countries. He was never taken to a proper medical centre to correct his condition nor was his mother ever given proper antenatal healthcare access. His background of being a poor person from rural India highlights the problems of inequalities in healthcare access.